Promoting Students’ Communication Skill through the Application of Project Based Learning - Farida Nova Kurniawati; Susanto Susanto; Ahmad Munir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The aim of this research is to describe how Project Based Learning promotes students’ ability to communicate ideas. Qualitative was used as the research method of this research. The subjects of this research were five students were chosen as the subject of this research. They were in the ninth grade in one of state Islamic schools in a relative big city. The researcher collected the data from observation and the recording video of the process of making the project which was wall magazine. All the data from observation were in the form of verbal data. After analyzing the data, the result shows the students can reach all of indicators of communicating ideas with eight examples as the evidences. In short, it can be concluded that Project Based Learning can promote students’ communication skill particularly students’ ability to communicate with others. Keywords: project based learning, communication skill